Internet of Things (IoT) Implementation in Tilapia Aquaculture: Profitability Assessment of Smart Pond Management in Subang District, West Java - Prahitaningtyas, Sherina (Politeknik Siber Cerdika Internasional, 2025)
This study aims to evaluate the effectiveness and profitability of implementing an Internet of Things (IoT)–based smart pond management system in tilapia aquaculture within Subang District, West Java. A controlled field experiment compared three IoT-enabled ponds equipped with real-time pH, temperature, dissolved oxygen, and turbidity sensors against three traditionally managed ponds (using manual monitoring) across a complete 120-day production cycle. Results show that IoT monitoring significantly improved water quality stability, increasing fish survival rates by 12.5% (from 80% to 92.5%), biomass production by 15.3%, and feed conversion efficiency by 8.7%, thereby enhancing operational performance. Economic analysis revealed that the IoT system produced favorable financial indicators, including higher Net Present Value (NPV), Internal Rate of Return (IRR), and Revenue–Cost (R/C) ratios, despite requiring a larger initial investment. These findings indicate that IoT adoption can provide substantial technical and economic benefits to smallholder aquaculture when applied under appropriate management conditions. Overall, the study concludes that smart pond systems represent a viable pathway for increasing productivity, reducing production risks, and improving profitability in Indonesian freshwater aquaculture.